الحلول الشرعية للديون المتعثرة في المصارف الإسلامية : بيت التمويل الكويتي في ماليزيا أنموذجا - دكو، محمد مصطفى موسى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The researcher aims to discover the possible legitimate (Shariah compliant) solutions to solve the phenomena of nonperforming debts (debt defaults) in Islamic banks, by selecting Kuwait Finance House (KFH) in Malaysia as a model for this study, taking into consideration the reasons that led to the loans defaults in Islamic Banks. Starting with the global financial crisis as a historical reason of financial distress in the word, which affected the Islamic banks including Kuwait Finance House in Malaysia. The researcher depended on the inductive approach to collect the early and contemporary scholars' opinions that are related to debts and their solutions from different sources directly relevant to nonperforming debts. He also used the analytical approach to analyst the various views about the legitimate solutions, to choose the Shariah and legal standpoint. In addition, the researcher used the comparative approach to combine the international standards in studying credit risks and its types, in comparison with the Shariah standards in order to get a valid alternative. With the help of the reports from KFH that reported to the Central Bank of Malaysia (BNM) in order to study the samples related to KFH about risk management and control and the quality of KFH relationship with BNM to determine to what extent to BNM support the such banks. The researcher found that the financial derivatives, and its types can be justified to be Shariah complaint, and the business guarantees and the delay penalties can be treated through emergency conditions of the depressing, inflation, and deflation. The researcher has excluded the commercial insurance and what it could be related to suspicious transaction. Finally, the researcher concluded his study with numerous suggestions, such as restructuring, merging, and trade selling to exit from the loans default and financial failure. In addition, the research encouraged KFHM to tilt to the programs for coordination and direct monitoring program of BNM, rather than the Kuwait Central Bank in all its activities. Disclosures with the analysts and the researchers to know the seriousness of its activities and quality of threats that the bank face to take necessary actions before increasing the risks.